2000
DOI: 10.1021/ma001245z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Poly(dimethylsiloxane) Mixtures with Silicate Nanoparticles

Abstract: Pulsed field-gradient (PFG) NMR has been used to measure self-diffusion coefficients in mixtures of silicate nanoparticles with poly(dimethylsiloxane)s as a function of volume fraction of particles and of polymer molecular weight. Two different sizes of nanoparticles were used: the smaller acted like a solvent, and the larger one acted more like a colloidal particle. In the former case, two distinct diffusion coefficients were obtained, corresponding to the particle and the polymer. In the second case, only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 19 publications
8
68
2
Order By: Relevance
“…It is not clear what mechanism causes the reduction of melt viscosity in the nanocomposites with low GO loading. One possibility is acting of GO sheets as plasticizer, increasing the free volume and therefore decreasing the melt viscosity [36]. Whereas at higher GO loading, the polymer-GO and GO-GO interactions are predominate and causes increase the melt bulk viscosity.…”
Section: Physical Properties Of Nanocompositesmentioning
confidence: 99%
“…It is not clear what mechanism causes the reduction of melt viscosity in the nanocomposites with low GO loading. One possibility is acting of GO sheets as plasticizer, increasing the free volume and therefore decreasing the melt viscosity [36]. Whereas at higher GO loading, the polymer-GO and GO-GO interactions are predominate and causes increase the melt bulk viscosity.…”
Section: Physical Properties Of Nanocompositesmentioning
confidence: 99%
“…Several publications cite these effects for polymer systems though the techniques and samples available for this work preclude a more detailed study. However, as we have shown in previous publications 19,20 a good qualitative description can be made by using the averaged relaxation time and these are the values plotted in the subsequent figures. Figure 6 shows plots of the spin-spin relaxation rate (1/T 2 ) as a function of molecular weight of the PDMS segment: reduced molecular mobility of polymers is indicated by an increase in relaxation rate.…”
Section: Diffusion Nmr Spectroscopymentioning
confidence: 74%
“…19,26 An acid-catalyzed polymerization of sodium silicate followed by a reaction with trimethylchlorosilane in a process described elsewhere 27 -using an equivalent molar ratio of trimethylsiloxy and silicate units-produced this amorphous nanoparticle with a weight-average radius of gyration of 1.5 nm and glass transition temperature of 96 ± 3 o C by dynamic mechanical thermal analysis.…”
Section: Trimethylsiloxy Polysilicate Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, uniformly dispersed nanoparticles reduce the entanglement of polymer chains while the blend viscosity reduces with the free volume associated with the nanoscale filler or particles, due to the rigid and stiff characteristics of the length sorted single-walled carbon nanotubes (SWNTs) rendering non-Einstein-like behavior. Roberts et al [11] found that clusters of silica caused viscosity reduction to the linear poly(dimethylsiloxane) when the nanoparticles were less than 0.7 nm in size, which facilitated plasticizing effects. Tuteja et al used PS nanoparticles and studied its viscosity reduction effect, at different molecular weights of the linear PS matrix [12].…”
Section: Introductionmentioning
confidence: 99%